ANALISIS YURIDIS ATAS PENGHENTIAN PENYELIDIKAN TINDAK PIDANA PEMALSUAN AKTA AUTENTIK DI DITRESKRIMUM POLDA KALBAR PADA TAHUN 2025 (Studi Kasus Laporan Polisi Nomor: LP/B/178/VI/2024/SPKT/Polda Kalimantan Barat) - NIM. A1012221015, RONI RAMADAN (Jurnal Fatwa Hukum, 2025)
ABSTRACT Following a report from Wahyu Hartoko, the plaintiff and heir of Sukartadji, to the Directorate of General Criminal Investigation (Ditreskrimum) of the West Kalimantan Regional Police, Police Report Number: LP/B/379/XII/2024/SPKT/Polda Kalbar, regarding the forgery of an authentic deed, police officers from the Directorate of General Criminal Investigation (Ditreskrimum) of the West Kalimantan Regional Police conducted an investigation. However, the investigation was ultimately terminated in 2025 on the grounds that the reported act did not constitute a crime, as stated in the letter of termination of investigation, issued by the Director of General Criminal Investigation of the West Kalimantan Regional Police, Letter Number: B/37/I/2025/Ditreskrimum, dated January 20, 2025, concerning Notification of Termination of Investigation. However, there is clear evidence supporting that when Notary/PPAT Evan Dari Rachman, S.H., M.Kn., issued the share sale and purchase deed No. 06 dated August 4, 2023, it was not based on the facts as seen, witnessed, and experienced in a legal act. The problem formulation in this study is: "What is the Reason for Terminating the Investigation of the Criminal Act of Forgery of Authentic Deeds in the Case of Police Report Number: LP/B/379/XII/2024/SPKT/Polda Kalbar?" Meanwhile, the purpose of the study is to reveal the normative basis that underlies the investigator's authority to terminate the investigation of the case of Police Report Number: LP/B/379/XII/2024/SPKT/Polda Kalbar and the reasons for terminating the investigation into the criminal act of forgery of authentic deeds in the case of Police Report Number: LP/B/379/XII/2024/SPKT/Polda Kalbar. The legal research method used by the author is a normative legal research method with a statute approach and a case approach. Based on the research results, it was concluded that the normative basis for the investigator's authority to terminate the investigation of Police Report Number: LP/B/379/XII/2024/SPKT/Polda Kalbar is Article 109 paragraph (2) of the Criminal Procedure Code, which states that termination may be carried out if the alleged incident is not a criminal act. The reason for terminating the investigation into the crime of falsifying an authentic deed in Police Report Number: LP/B/379/XII/2024/SPKT/Polda Kalbar is that the reported act does not constitute a crime because it does not contain elements of the crime of falsification as referred to in Article 263 and/or Article 264 and/or Article 266 of the Criminal Code and legally the issuance of a letter of termination of investigation is valid according to law, especially the provisions of Article 109 paragraph (2) of the Criminal Procedure Code. However, if investigators summon and request information from the Vincensius Singkawang Hospital regarding Sukartadji's health condition, then it is very likely that this case will not be terminated by investigation (SP2LID). Keywords: Termination of Criminal Investigation, Forgery, Authentic Deed. ABSTRAK Adanya laporan dari Wahyu Hartoko sebagai Pelapor yang merupakan ahli waris dari Sukartadji ke Direktorat Reserse Kriminal Umum (Ditreskrimum) Polda Kalbar dengan Laporan Polisi Nomor: LP/B/379/XII/2024/SPKT/Polda Kalbar terkait terjadinya tindak pidana pemalsuan akta autentik, maka aparat Kepolisian dari Direktorat Reserse Kriminal Umum (Ditreskrimum) Polda Kalbar melakukan penyelidikan terhadap kasus tersebut. Namun proses penyelidikan ini akhirnya dihentikan pada tahun 2025 dengan alasan bahwa perbuatan yang dilaporkan bukan merupakan tindak pidana sebagaimana dalam surat penghentian penyelidikan melalui Surat Direktur Reskrimum Polda Kalbar Nomor : B/37/I/2025/Ditreskrimum tanggal 20 Januari 2025 Perihal Pemberitahuan Penghentian Penyelidikan. Akan tetapi secara nyata terdapat bukti-bukti yang mendukung bahwa pada saat Notaris/PPAT Evan Dari Rachman, S.H., M.Kn., mengeluarkan akta jual beli saham No. 06 tanggal 4 Agustus 2023 tersebut tidaklah berdasarkan fakta-fakta sebagaimana yang dilihat, disaksikan dan dialaminya dalam suatu perbuatan hukum. Rumusan masalah dalam penelitian ini adalah: “Apa Yang Menjadi Alasan Penghentian Penyelidikan Tindak Pidana Pemalsuan Akta Autentik Dalam Kasus Laporan Polisi Nomor: LP/B/379/XII/2024/SPKT/Polda Kalbar ?”. Sedangkan tujuan penelitian adalah untuk mengungkapkan landasan normatif yang menjadi dasar kewenangan penyidik dalam menghentikan penyelidikan kasus Laporan Polisi Nomor: LP/B/379/XII/2024/SPKT/Polda Kalbar dan alasan penghentian penyelidikan terhadap tindak pidana pemalsuan akta autentik dalam kasus Laporan Polisi Nomor: LP/B/379/XII/2024/SPKT/Polda Kalbar. Metode penelitian hukum yang digunakan penulis adalah metode penelitian hukum normatif dengan pendekatan undang-undang (statute approach), dan pendekatan kasus (case approach). Berdasarkan hasil penelitian, maka diperoleh kesimpulan bahwa landasan normatif yang menjadi dasar kewenangan penyidik dalam menghentikan penyelidikan kasus Laporan Polisi Nomor: LP/B/379/XII/2024/SPKT/Polda Kalbar adalah Pasal 109 ayat (2) KUHAP, yang menyatakan bahwa penghentian dapat dilakukan jika peristiwa yang disangkakan bukan tindak pidana. Alasan penghentian penyelidikan terhadap tindak pidana pemalsuan akta autentik dalam kasus Laporan Polisi Nomor: LP/B/379/XII/2024/SPKT/Polda Kalbar bahwa perbuatan yang dilaporkan bukan merupakan tindak pidana karena tidak terdapat unsur tindak pidana pemalsuan sebagaimana dimaksud dalam Pasal 263 dan/atau Pasal 264 dan/atau Pasal 266 KUHP dan secara yuridis terbitnya surat penghentian penyelidikan adalah sah menurut hukum, khususnya ketentuan Pasal 109 ayat (2) KUHAP. Namun, apabila penyidik memanggil dan meminta keterangan dari pihak Rumah Sakit Vincensius Singkawang mengenai kondisi kesehatan Sukartadji, maka kasus ini kemungkinan besar tidak dilakukan penghentian penyelidikan (SP2LID). Kata Kunci : Penghentian Penyelidikan Tindak Pidana, Pemalsuan, Akta Autentik.